Prospective Validation Obtained in a Similar Group of Patients and with Similar High Throughput Biological Tests Failed to Confirm Signatures for Prediction of Response to Chemotherapy and Survival in Advanced NSCLC: A Prospective Study from the European Lung Cancer Working Party - Berghmans, Thierry; Ameye, Lieveke; Lafitte, Jean-Jacques; Colinet, Benoît; Cortot, Alexis; CsToth, Ingrid; Holbrechts, Stéphane; Lecomte, Jacques; Mascaux, Céline; Meert, Anne-Pascale; Paesmans, Marianne; Richez, Michel; et al. (Frontiers in Oncology, 2015)
Aim: Cisplatin doublets are standard 1st line treatment for advanced non small cell lung cancer (NSCLC), without accurate predictor for response and survival, but important toxicity. Our aims were to identify predictive (for response) and prognostic (for survival) biological signatures in patients with NSCLC using mRNA and miRNA expression. Methods: Patients with pathologically proven untreated NSCLC, receiving 1st line cisplatin-vinorelbine and with an assessable lesion were eligible. A bronchial biopsy was lysed into Tripure Isolation Reagent on ice, snap frozen and stored at -80°C. mRNA expression was analysed using microarrays Agilent Technologies. miRNA expression was assessed using TaqMan Low Density Arrays (756 human miR panel, Applied Biosystems). Validation was performed by RT-PCR on the selected genes. Survival was measured from the registration date and response assessed by WHO criteria. Results: Biopsies for transcriptomic analyses were obtained from 60 consecutive patients. No statistically significant differences were observed according to the main clinical characteristics, response rate (43% vs 41%) or survival (median 25 vs 29 months) between derivation and validation sets. In the derivation set (n=38 patients), two mRNA and one miRNA predictive signatures for response were obtained. One mRNA and one miRNA prognostic signatures were derived from the first set, allowing an adequate distinction of patients with good and poor overall and progression-free survivals. None of these signatures could be validated in the validation set (n=22 patients). Conclusions: In this prospective study with advanced NSCLC treated with cisplatin-vinorelbine, we were able to derive with high throughput techniques predictive and prognostic signatures based on transcriptomic analyses. However, these results could not be reproduced in an independent validation set. The role of miRNA and mRNA as predictive or prognostic factors remains a research topic and the use of high thro